2002
DOI: 10.1148/radiol.2242011412
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Motility: Comparison of Assessment with Real-Time MR Imaging or Barostat Measurement—Initial Experience

Abstract: Measurements of gastric volume and motility with magnetic resonance (MR) imaging were compared with simultaneously performed measurements with a barostat in six healthy volunteers. Three-dimensional volume and two-dimensional dynamic MR images and barostat measurements were obtained at rest. Alterations in gastric volume and motility were induced by means of infusion of glucagon and erythromycin, respectively. There is strong evidence to have the opinion that MR imaging is as accurate as barostat measurement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
1
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 19 publications
1
70
1
6
Order By: Relevance
“…Total gastric volume was calculated by adding intragastric air and contents volumes. This method has been described previously (8).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Total gastric volume was calculated by adding intragastric air and contents volumes. This method has been described previously (8).…”
Section: Discussionmentioning
confidence: 99%
“…The multilumen catheter was elongated with a 3-m-long catheter (16 Fr) allowing the barostat device to be placed out of the vicinity of the MRI device. A previous study has shown that elongation of the multilumen catheter does not influence MDP, nor does it influence intragastric bag volume (8). The barostat device keeps the pressure in the intragastric bag at a preselected level.…”
Section: Gastric Barostatmentioning
confidence: 99%
See 3 more Smart Citations